Telecommunication Systems Principles and Applications of Wireless-Optical Technologies - Alimi, Isiaka A.; Monteiro, Paulo P.; Teixeira, António L. (IntechOpen, 2019)
This book is based on both industrial and academic research efforts in which a number of recent advancements and rare insights into telecommunication systems are well presented. The volume is organized into four parts: "Telecommunication Protocol, Optimization, and Security Frameworks", "Next-Generation Optical Access Technologies", "Convergence of Wireless-Optical Networks" and "Advanced Relay and Antenna Systems for Smart Networks." Chapters within these parts are self-contained and cross-referenced to facilitate further study.